Effects of a school-based intervention program for adolescents with a special focus on the overweight/obese population [Efekty školního intervenčního programu pro adolescenty se zaměřením na populaci s nadváhou/obezitou] - Michal Kudláček; Lisa Carla James (Acta Universitatis Palackianae Olomucensis. Gymnica, 2011)
BACKGROUND: Obesity has become a pandemic, with more than a billion people affected worldwide. During the past two decades, the prevalence of obesity in children has risen greatly throughout the entire world. This is especially alarming in youth where the new prevalence is above predicted trends. OBJECTIVE: This study was aimed at providing an intervention program for adolescents in the category of overweight/obese in accordance with physical activity (PA) guidelines. The total duration of the project was 8 weeks. The purpose of the study was to assess the effects of the intervention and promote lifelong participation in physical activities. METHODS: The research sample was made up of high school students chosen in accordance with selected criteria of BMI between 25 ≥ 35.5 (n = 27). Data was collected from the participants through the use of questionnaires, internet, and pedometers, as well as objective measurements of height, fat and BMI using the Tanita Body Composition Analyzer. RESULTS: Results showed that there was no reduction in BMI. There was also an increase in the amount of vigorous activity and number of steps throughout the intervention. The logical significance of 240 METminutes per week was seen in their study, whereas in our study we noticed a four times greater increase with 957 METminutes per week, and logical significance in all areas. CONCLUSIONS: In conclusion it was noted that increased activity reduces a sedentary lifestyle, while it improved social, mental and health status. In addition, our data indicate that sedentary behaviors are strongly related to overweight/obesity in adolescents. It also demonstrates that the type of model implemented with the intervention must reflect a holistic role and activities must critically reflect the interest and preferences of the participants, so that motivation to proceed is strong and conditions for adherence could be set up. [VÝCHODISKA: Z obesity se stala pandemie, která celosvětově ovlivňuje přes miliardu lidí. Prevalence obezity za posledních dvacet let dramaticky stoupla, a to celosvětově. Tento fakt je obzvláště alarmující u mládeže, kde se statistiky prevalence dostávají nad predikované trendy. CÍLE: Tato studie byla zaměřena na sestavení základního intervenčního programu pohybové aktivity (PA) pro adolescenty, spadající do kategorie nadváha/obesity. Celková délka programu byla 8 týdnů. Tvorba programu proběhla v souladu s oficiálními doporučeními pro pohybovou aktivitu. Účelem studie bylo ohodnocení efektivity intervence a podpora celoživotní účasti participant na pohybové aktivitě. METODIKA: Výzkumný soubor byl tvořen středoškolskými studenty. Kritériem pro výběr participantů byla BMI kategorizace 25 ≥ 35.5. Velikost výzkumného souboru byla 27 jedinců. Pro posouzení efektivity intervence bylo použito pre-test a post-test měření. Hlavními intervenčními nástroji byly dotazníky, internet (facebook), pedometry a přístroj Tanita, využívaný k měření tělesného složení. VÝSLEDKY: Výsledky nepotvrdily snížení hodnot BMI. Dále jsme zaznamenali zvýšené množství intenzivní PA a počtu kroků v průběhu celého projektu. Věcná významnost rozdílu v úrovni PA byla stanovena na úrovni 240 MET-minut/týden. V naší studii jsme zaznamenali nejnižší nárůst PA o > 957 MET-minut/týden u všech druhé PA. ZÁVĚRY: Zvýšená pohybová aktivita redukuje sedavý životní styl, zlepšuje společenský, psychický a zdravotní status. Sedavý způsob života významně souvisí s nadváhou a obezitou u populace adolescent. Způsob prezentace a zvolený intervenční model by měl splňovat prvky komplexnosti a kriticky reflektovat zájmy a preference participantů, a to především z důvodu zvýšené motivace a následně adherence.]